2014
DOI: 10.1016/j.cgh.2013.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Evidence and Recommendations for Imaging Liver Fat in Children, Based on Systematic Review

Abstract: Background & Aims Fatty liver is a common problem in children, and increases their risk for cirrhosis, diabetes, and cardiovascular disease. Liver biopsy is the clinical standard for diagnosing and grading fatty liver. However, non-invasive imaging modalities are needed to assess liver fat in children. We performed a systematic review of studies that evaluated imaging of liver fat in children. Methods We searched PubMed for original research articles in peer-reviewed journals from January 1, 1982 through Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 38 publications
2
100
0
2
Order By: Relevance
“…In addition, elevated serum ALT, defined as two times the upper limit of normal, was shown in overweight and obese children to have a sensitivity of 57% and specificity of 71% for NAFLD [8]. Moreover, liver ultrasound evidence of steatosis has been shown to have a positive predictive value of only 47–62% for NAFLD [9]. The advanced MRI technique of proton density fat fraction has been shown to strongly correlate with hepatic steatosis, but there is not yet standardization for clinically appropriate cut-offs to determine NAFLD [10].…”
Section: Nutritionmentioning
confidence: 99%
“…In addition, elevated serum ALT, defined as two times the upper limit of normal, was shown in overweight and obese children to have a sensitivity of 57% and specificity of 71% for NAFLD [8]. Moreover, liver ultrasound evidence of steatosis has been shown to have a positive predictive value of only 47–62% for NAFLD [9]. The advanced MRI technique of proton density fat fraction has been shown to strongly correlate with hepatic steatosis, but there is not yet standardization for clinically appropriate cut-offs to determine NAFLD [10].…”
Section: Nutritionmentioning
confidence: 99%
“…First, fatty liver disease prevalence in children is high (1820), and so reliable methods to non-invasively assess fatty liver disease in children are needed. Ultrasound has been used to assess hepatic steatosis (21, 22), but a recent systematic review has shown that it has limited accuracy to diagnose and grade pediatric hepatic steatosis (23). Second, children are different from adults in important characteristics relevant to MRI including ability to tolerate MRI examinations, breath-holding capacity, and body habitus.…”
Section: Introductionmentioning
confidence: 99%
“…Second, children are different from adults in important characteristics relevant to MRI including ability to tolerate MRI examinations, breath-holding capacity, and body habitus. These characteristics influence the feasibility, technical optimization, and quality of MRI and may affect its diagnostic performance (23, 24). …”
Section: Introductionmentioning
confidence: 99%
“…A systematic review conducted in 2014, based on the available studies in children, shows the positive predictive value of US to be between 47 to 62% in detecting and grading fatty liver in children. The sensitivity for revealing mild steatosis in adults is lower than for other grades, whereas high quality studies are lacking in children (16). Fibrosis and inflammation may also intensify liver echogenicity, but they are associated with liver enlargement more often than simple steatosis.…”
Section: Fatty Livermentioning
confidence: 99%